How do health workers build resilience after family loss, covid-19 infection, and social stigma during the pandemic? - Taniasar, Nungky; Handoyo, Seger; Suhariadi, Fendy; Dinda Nadia, Fiona Niska (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study investigates the resilience-building process of health workers who experienced critical incidents during the COVID-19 pandemic, including family loss, personal infection, and social stigma. Specifically, the research addresses how these factors influence the psychological, emotional, and behavioral resilience of healthcare workers. Using a qualitative method with a Critical Incident Technique design, the study involved in-depth interviews with 12 health workers, including nurses and medical professionals, who met the criteria of having lost a spouse or parent to COVID-19, endured moderate to severe infection, or faced negative community stigma. The interviews were analyzed using thematic analysis to identify key themes and resilience factors. Findings reveal that social support, emotional regulation, self-efficacy, and spirituality played significant roles in resilience-building. Affective responses, such as a sense of security from social support and optimism, cognitive responses like positive thinking and acceptance, and behavioral capacities, including increased worship and professionalism, were prominent. The research also highlights that these resilience processes led to positive adaptation and post-traumatic growth, with 33% of participants reporting a more positive outlook on life and 66% exhibiting increased patience and gratitude. These findings suggest that resilience in healthcare workers is shaped by a complex interplay of emotional, cognitive, and behavioral factors, with implications for policy development and mental health support for healthcare professionals.